Training and Mentoring of Making Corn Catfish Nougat in Sambiyan Village, Bangkalan, Madura - Rosida; Diah Hari Suryaningrum; Ulya Sarofa (Nusantara Science and Technology Proceedings)
In the training and mentoring of corn and catfish processing products in Sambiyan Village, Bangkalan Madura aimed to increase the knowledge and skills the member of farmer women grup “Melati” as a nougat product which had high selling value so that it could give benefit to them. The implementation method that was used in this activity was discussion about the problem of the village, training, and mentoring so it could give a solution to the problem faced by society. The added value for the community service program was endeavoring the housewife of farmers to use their spare time by making corn-catfish nougat which was easy to make and useful for their welfare. Base on the implementation of the program, it revealed improving the knowledge and skill of people in making corn-catfish nougat. In conclusion, this community service could support and assist the partner to create a positive effect on autonomy and increased people's productivity.